Annual glycemic variations and risk of cancer among Chinese patients with type 2 diabetes mellitus: A population-based cohort study in Shanghai. (January 2021) - Xu, Huilin; Zhang, Fen; Xu, Wanghong; Li, Jun; Zhu, Jingjing; Zhang, Minlu; Wu, Zhenyu; Qin, Guoyou
Abstract: Background: Long-term glycemic variation in diabetes patients may have contributed to cancer incidence. Aim: In this study we aimed at the association between annual glycemic variation and the risk of cancer in Chinese patients with type 2 diabetes mellitus (T2DM). Methods: Subjects of this study were from an established population-based cohort of T2DM patients in Minhang District of Shanghai, China. Incident cancer were obtained from the Shanghai Cancer Registry. Glycemic variation was evaluated using the annual fasting glucose coefficient of variation (FG-CV), which was used as a time-dependent variable in a Cox regression model to estimate the associations with the cancer risk. Restricted cubic splines were used to explore potential non-linear associations. Results: A total of 2, 140 incident cancers (1100 men and 1040 women) were identified from the 46, 202 diabetes patients during 12-year follow-up. The annual FG-CV remained significantly associated with an increased risk of cancer, even after adjusting for the annual mean FG level. A significant non-linear association was found in male T2DM patients, and a significant linear association in female patients. Conclusions: The positive association of the annual FG-CV with the risk of cancer in T2DM patients indicate the importance to stabilize the FG level.